Sick building syndrome and mental health among university laboratory staffs - Md Saad, Zuliza; Rasdi, Irniza; Zainal Abidin, Emilia (Malaysian Public Health Physicians' Association, 2017)
The aim of this study was to determine the prevalence of sick building syndrome (SBS) and other factors contributing to probable mental health problems among university laboratory staffs. A cross-sectional study was conducted among 264 laboratory staffs in UPM. Data was collected using validated self-administrated questionnaires consists of Job Content Questionnaire (JCQ), General Health Questionnaire (GHQ) and SBS. Data was analyzed using SPSS version 22.0. In total, about 28% of the participants reported having probable mental health problems. The prevalence of SBS was 31.4%. After controlling for confounders, the significant factors for probable mental health problems were job insecurity (AOR 2.33, 95% CI 0.212-0.867), job demand (AOR 1.12, 95% CI 0.445-0.921), fatigue (AOR 0.94, 95% CI 0.162-1.425), drowsiness (AOR 0.75, 95% CI 1.023-4.647) and household income (AOR 0.339, 95% CI0.166-0.995). Results visibly showed that psychosocial factors and symptoms of SBS at their working environment contribute to probable mental health problems among laboratory staffs. The strongest predictors in this study were job insecurity. Hence, further assessment and preventive measures should be carried out to reduce the risk factors of probable mental health problems and to improve working environment among university laboratory staffs.